Finegoldia magna, an Anaerobic Gram-Positive Bacterium of the Normal Human Microbiota, Induces Inflammation by Activating Neutrophils - Neumann, Ariane; Björck, Lars; Frick, Inga-Maria (Frontiers in Microbiology, 2020)
The Gram-positive anaerobic commensal Finegoldia magna colonizes the skin and other non-sterile body surfaces, and is an important opportunistic pathogen. Here we analyzed the effect of F. magna on human primary neutrophils. F. magna strains ALB8, 312 and 505 as well as their associated proteins FAF and protein L activate neutrophils to release reactive oxygen species. Co-incubation of neutrophils with the bacteria leads to a strong increase of CD66b surface expression, another indicator for neutrophil activation. Furthermore, all tested stimuli triggered the release of NETs from the activated neutrophils. This phenotype is dependent on actin rearrangement, NADPH oxidases and the ERK1/2 pathway. Proteins FAF and L also induced the secretion of several pro-inflammatory neutrophil proteins; HBP, IL-8 and INFγ. This study shows for the first time a direct interaction of F. magna with human neutrophils and suggests that the activation of neutrophils plays a role in F. magna pathogenesis.